Laboratory measurements of light scattering properties of kaolinite dust at 532 nm. Issue 6 (3rd June 2018) - Li, Ron; Tang, Guanglin; Ding, Jiachen; Logan, Timothy; Brooks, Sarah D.; Collins, Don R.; Yang, Ping; Kattawar, George W.
ABSTRACT: Light scattering by kaolinite dust samples at 532 nm is studied using a newly developed laboratory apparatus. During the experiments, dust samples are suspended in water, aerosolized by a nebulizer, and then injected into the scattering zone, with or without going through a diffusion drier, to generate either dried dust particles or water droplets with dust inclusions. The light source is a dual wavelength (532 and 1064 nm) diode-pumped solid state laser. Light scattered by an ensemble of particles is collected by a charge-coupled device (CCD) camera, which is mounted on the rotating arm of a stepper motor. The stepper motor rotates the CCD to cover the scattering angle range from 3° to 177°. Polarized scattering light is measured for the horizontally and vertically polarized incident light. The apparatus is calibrated, using pure water droplets as the scattering media. The response function with respect to the scattering angle is obtained by comparing the measurements with Lorenz–Mie calculations and then used in the later data analysis. Measurements show that the backward scattering features of the water droplets are smoothened due to their dust inclusions. Numerical simulations and measurements are extensively compared and discussed. It is found that the Lorenz–Mie theory is inadequate to reproduce the scattering phase functions of either dust particles or water droplets with dust inclusions. A nonspherical aggregate model is applied to simulate the scattering phase functions. The simulation is able to reproduce the overall scattering features; however, substantial discrepancies still exist due to uncertainties in particle shape and refractive index. Copyright © 2018 American Association for Aerosol Research